Simulation hydraulique des écoulements dans un canal d’irrigation de la fin du IVe millénaire en Oman - Bertrand-Krajewski, Jean-Luc; Pouzol, Tanguy; Brochier, Jacques Elie; Baudet, Robinson; Castel, Corinne (Techniques Sciences Méthodes, 2025)
Une mission archéologique pluridisciplinaire conduite par Corinne Castel, sous l’égide du CNRS, de l’Université Lyon 2 et du Ministry of Heritage and Tourism of Oman, mène des fouilles au Sultanat d’Oman depuis 2019 sur le secteur d’Al-Arid. Ce secteur est situé sur la rive gauche du wadi Khuwaybah, dans une large vallée au pied des monts Al-Hajar, à une quinzaine de kilomètres au nordouest du site archéologique de Bāt classé au patrimoine mondial de l’Unesco. Les fouilles ont mis en évidence deux phases principales d’occupation du site d’Al-Arid au début de l’âge du Bronze, aux périodes Hafit (environ 3200-2700 avant notre ère) puis Umm an-Nar (environ 2700-2000 avant notre ère). Elles ont révélé un nombre remarquable de vestiges : sept tours, une nécropole, des bâtiments, un atelier de transformation du minerai de cuivre en métal de la période Hafit.
Keywords: Archéologie – Oman; Irrigation – Oman

The Aflaj of Wadi al-Jizzi, Oman - Milwright, Marcus (Encounters: Medieval Islamic History in 50 Objects, 2025)
This book consists of fifty case studies and offers an innovative approach to the study of Medieval Islamic history, concentrating on the analysis of physical objects from the seventh to the eighteenth centuries and across most of the regions that make up the pre-Modern Islamic world.These include a wide range of objects from portable items like coins, vessels and books to major constructions, including mosques, tombs, castles, dams, and canal systems. The central argument is that the interdisciplinary study of physical objects provides invaluable perspectives that can deepen or challenge the evidence in the written record. Object-based study can also shed light on the lives of social groups who are seldom discussed in Islamic texts written before the modern period. To demonstrate these points, each case study focusses on a single object or small group of related objects. The case studies combine close analysis of the material and visual characteristics with a discussion of the wider context in which such objects were commissioned, made, used, adapted and exchanged.The book is intended as an introduction to the historical study of Islamic objects, employing perspectives from the fields of art history, archaeology, numismatics, ethnography, and epigraphy. Written with a minimum of technical language and supported by a critical introduction, an extensive glossary, a timeline and guide for further reading, the book is aimed at students and general readers who are interested in the political, economic, social, cultural, religious and intellectual histories of the Islamic world.
Keywords: Irrigation – Oman

وكيل الفلج (حضارة، نظم ري، عُمان) - السالمي, عبد الله بن محمد; بحاز, إبراهيم بن بكير; السالمي, عبد الرحمن بن سليمان; بن ادريسو, مصطفى بن محمد (معجم مصطلحات الإباضية: العقيدة، الفقه، الحضارة, 2012)
المسؤول الأول عن إدارة الفلج، ومهامه تنظيم أحوال الفلج وإزالة الأتربة عن سواقيه، وبيع ثمار أمواله، وإيجار الماء المخصص لمصالحه، وقبض وصاياه وإدارة أوقافه. والعدالة في التقسيم هو المقصد الأساس الذي يحكم عمل الوكيل. وكيل الفلج في عُمان يشبه «لاوَمْنَا» في نظام تقسيم مياه الأمطار بوادي مزاب.
Keywords: Irrigation – Oman

عريف الأفلاج (حضارة، نظم ري، عُمان) - السالمي, عبد الله بن محمد; بحاز, إبراهيم بن بكير; السالمي, عبد الرحمن بن سليمان; بن ادريسو, مصطفى بن محمد (معجم مصطلحات الإباضية: العقيدة، الفقه، الحضارة, 2012)
المسؤول عن نظام الري بالأفلاج في عُمان، يُختار لخبرته ودرايته بقضايا المياه. ومهمّته السهر على انضباط تقسيم نوبات المياه بالعدل على حسب مساحات الأراضي المسقية والحقوق المتعينة. من مهامه كذلك فض النزاعات بين المتخاصمين في حقوق هذه المياه.
Keywords: Irrigation – Oman

حريم منبع الفلج (حضارة، نظم ري، عُمان) - السالمي, عبد الله بن محمد; بحاز, إبراهيم بن بكير; السالمي, عبد الرحمن بن سليمان; بن ادريسو, مصطفى بن محمد (معجم مصطلحات الإباضية: العقيدة، الفقه، الحضارة, 2012)
حريم يقدر بعد استفراغ ماء الأصل بثلاثمائة ذراع، وقيل: خمسمائة ذراع، وقيل: مقداره ما لا يضر به.
Keywords: Irrigation – Oman

Engineering Thoughts Embedded in Ancient Groundwater Techniques: The Case of Falaj in Oman - Mohtashami, Ali; Ghafri, Abdullah Saif al-; Labbaf Khaneiki, Majid (Iranian Journal of Science and Technology, Transactions of Civil Engineering, 2025)
This study aims to examine the engineering design of the falaj system using a wide variety of published documents on its construction and maintenance. A falaj is a hand-dug tunnel that transfers groundwater from aquifers to lower-lying lands. Falaj masters, despite the fact that they are usually illiterate, employ embedded mathematics to calculate the height difference between two points, excavate tunnels, measure tunnel gradient and depth, and locate groundwater infiltration area. Their traditional knowledge is awash with a great deal of mathematical methods, which has turned falaj into a feat of engineering. These methods are primarily based on principles such as proportion, right triangles, similarity of triangles, the intercept theorem, unit conversion, fractions, algebraic equations, and the four basic operations. This study concludes that the technical complexity of falaj system in terms of engineering, is the result of some simple yet effective mathematical calculations that form the core of falaj indigenous knowledge and aflaj masters perceive such equations intuitionally.
Keywords: Irrigation – Oman

Quality Prediction of Sustainable Groundwater Resources, a Falaj in Oman - Mohtashami, Ali; Ghafri, Abdullah Saif Al-; Abri, Zahra Saif al- (Water Conservation Science and Engineering, 2024)
Aflaj are the most important engineering technology in Oman for the abstraction of water under the ground. Aflaj’s water is used for domestic and agricultural purposes in this country. Therefore, the quality of Aflaj’s water is crucial for both domestic users and farmers for agricultural and irrigation purposes. Water decision-makers consistently recognize the need for a reliable model that can predict quality. This study employs four distinct models to achieve this objective. Artificial neural network, adaptive neuro-fuzzy inference system (ANFIS), K-nearest neighbor, and support vector machine are the engaged models. They have been used for the forecasting of electrical conductivity (EC) as a quality parameter in falaj Al-Hamra, Oman. To this end, five reasonable scenarios are defined (S1, S2, S3, S4, and S5). Input data such as precipitation, flowrate of falaj, temperature of water, and EC values with lag time is the only difference among these scenarios. The data collection spans from 1982 to 2021. We implement these models using the MATLAB programming software. We also use four evaluation criteria, namely, mean absolute error, root-mean-square error, Nash–Sutcliff error, and R, to assess the performance. Results showed that, among all the models, ANFIS has the highest accuracy in all stages, including training, testing, and validation. All evaluation criteria indicate this. Also, findings were presented that S4 is closer to the real condition of falaj Al-Hamra, as the errors achieved from this scenario are less than the others. It means that there is a relationship between the contributing parameters in scenario #4 and the quality of water in falaj Al-Hamra. The funding also revealed that changes in flowrate have a greater impact on the water's EC than precipitation. This study assists water decision-makers in developing a well-functioning model for quality forecasting, which can then be enforced in falaj Al-Hamra.
Keywords: Irrigation – Oman

The History of Falaj Water Management in Northern Oman Case Study: the Falaj Al-Khatmain in Birkat Al Mouz - Saqri, Nasser A. Al- (2023)
This presentation sheds light on the system of water management and distribution of the aflaj in Oman through the case study of Falaj Al-Khatamein in Birkat Al-Mouz, which has been registered on the UNESCO World Heritage List since 2006. The lecture will start with an introduction to the historical background of the aflaj system. "Aflaj" (plural Falaj) is a gently sloping subterranean tunnel that drains out groundwater and conveys it onto the earth surface and all falaj systems in Oman are divided into three groups; Dawoodi Falaj, Ayni Falaj and Ghaili Falaj in northern Oman, the typology of aflaj, their cultural significance in the Omani society and their connection to different aspects of life in the past. The presenter will also talk about the management of aflaj water and the methods of distributing the water shares of aflaj. He will address various aspects connected to the aflaj system, including the irrigation cycle of falaj in the region/village and the daily division of the falaj water shares. Also the methods and tools for measuring irrigation time will be explained, for which a special sundial (Lamad) is necessary during the daytime and traditional star gazing at nighttime. The last part of the presentation will examine Falaj Al-Khatamein. The presenter will discuss the historical background of this falaj and the Birkat Al Mouz area, and will also explain the reasons behind the selection of this falaj and its management system for this study. Moreover, the social and economic aspects of this falaj and their impacts on society will be discussed, and it will be spelled out how the falaj has contributed to social harmony in the area.
Zentrum Moderner Orient (ZMO)
Keywords: Irrigation – Oman

Falaj Indigenous knowledge in Oman and Iran - Ghafri, Abdullah Saif Al-; Khaneiki, Majid Labbaf; Saqri, Nasser A. Al-; Kindi, Khalifa M. Al- (AlterNative: An International Journal of Indigenous Peoples, 2023)
Both Oman and Iran possess a harsh environment where people’s survival and development entail a deep knowledge about their surroundings. A considerable part of this knowledge has crystallized around the falaj, a hydraulic technique that transfers water from a groundwater source or seasonal runoffs to cultivated lands, in Omani and Iranian oases, that has historically served as the only water source in an otherwise barren arid land. This article argues that the spatial extent of the falaj confronts local communities with a variety of questions to be solved. This article also tries to answer how the falaj system contributed to the development of modern sciences in a broader context. The article concludes that a transition from Indigenous knowledge to modern sciences has changed the position of local communities from coexistence to over-exploitation in terms of their water resources, and this transition can explain their current water problems.
Keywords: Irrigation – Oman

Regard sur les paysages des sociétés hydrauliciennes du Moyen-Orient à travers les techniques de médiation identifiables a Nizwa (Oman) : aflaj et qanat - Megdiche, Fairouz (Sorbonne Université, 2015)
Keywords: Irrigation – Oman

Falaj Communities in Oman: A Case for Local Governance?: Ibāḍī Legal Rulings and Spatial and Ethnohistorical Observations - Bandyopadhyay, Soumyen; Mershen, Birgit (Journal of Material Cultures in the Muslim World, 2022)
This contribution studies the complex arrangement of legal, socio-economic, and technical aspects of the aflāj (s. falaj) water distribution and irrigation system, and how they have shaped communities and built environments in Oman, where the falaj has provided the virtual lifeline of oasis life since the first millennium BCE. Three case studies of falaj communities are presented, Birkat al-Mawz, al-Ḥamrāʾ, and Misfāt al-ʿAbrīyin, which developed during the prosperous early-Yaʿrubi period in the mid-eleventh/seventeenth century. It investigates the extent to which the Ibāḍī-Islamic legal framework allowed flexibility for the local governance, management, and organisation of this ancient system, and its adaptation to diverse demographic, environmental, and emergent socio-political conditions.
Keywords: Irrigation – Oman

الأفلاج في سلطنة عمان - ابراهيم, وفيق محمد جمال الدين (مؤسسة الكويت للتقدم العلمي, 2006)
Keywords: Irrigation – Oman

The Social Importance and Continuity of Falaj Use in Northern Oman - Sulaimani, Zaher bin Khalid al-; Helmi, Tariq; Nash, Harriet (2007)
Keywords: Irrigation – Oman

الافلاج في سلطنة عمان - منخي, سعدية عاكول; وفيق, هند فوزي (مجلة الآداب, 2014)
Keywords: Irrigation – Oman

Management of water shares for Falaj al-Hamra and Falaj al-Kasfa - Shaqsi, Saif Rashid al-; Nash, Harriet (Journal of Oman Studies, 2011)
Keywords: Irrigation – Oman

سلوت ونشوء الأفلاج في عُمان - Wilkinson, John Craven (التفاهم, 2005)
Keywords: Irrigation – Oman